Optimizing Students’ Reading Skills through Microlearning with Canva: A Digital Approach in ELT - Fitra Pinandhita; Mohd Hanafi bin Mohd Yasin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: Microlearning is sufficiently flexible to support various learning modalities and can be tailored to individual student needs. By making it easily accessible, teachers enable students to select concise, desired, necessary, and relevant information. Using microlearning enhances students' comprehension and retention, particularly in vocabulary development. Through Canva, analysis shows that this technology is beneficial for delivering microlearning. This research aims to assess the effectiveness of using the interactive visual design application Canva in English learning through microlearning. Method: The research subjects consist of 18 SMP Alam Nurul Furqon ninth-grade students. The study used qualitative methods with several instruments, including Google Forms, observation, and literature review. Results: The study reveals that students, by a percentage of 3.94, preferred using Canva as a learning medium compared to conventional teaching methods, and a percentage of 3.22 felt an increase in reading skills. This demonstrates that digital technology significantly influences various elements, including education, in today's era. Novelty: These results serve as a valuable reference for educators, indicating the students` high motivation levels and guiding efforts to enhance reading skills in English education in the future.